CRITICAL EVALUATION OF EU MIGRATION POLICY IN CRISIS AGENDA WITHIN FRAMEWORK OF BORDER MANAGEMENT - Mammadov, Sahil (Annals of Spiru Haret University. Economic Series, 2022)
If we try to define the concept of migration, which is one of the critical issues faced by all countries today, we will see that it is more a search for innovation stemming from a "problem", and this process has tried to preserve this feature from the very beginning of history until today. When we open the concept of "problem" here, it can be seen that sometimes there can be a direct threat to human existence, such as natural disaster, war, oppression and persecution, and sometimes this process can occur for personal reasons, such as unemployment, the desire for a better life. At the same time, the issue of migration can be considered optional as well as mandatory within the framework of interstate agreements and various difficulties experienced. It is known that the migration crisis observed in 2015 as a result of the fragmentation trend among the member states turned into an integration crisis in the EU migration policy. In this regard, this study aims to reveal the validity of independent national policy requirements by analyzing them. The secondary data methods have applied for this study by using different official sources from EU and other statistical sources. With this aim, the evaluation of the EU's migration policy goals, financial, legal and institutional tools in the context of inter-national and intergovernmental tension in the example of border management is considered as the main final goal of the study.